PTH Predicts the in-Hospital MACE After Primary Percutaneous Coronary Intervention for Acute ST-Segment Elevation Myocardial Infarction - Wu ZF; Su WT; Chen S; Xu BD; Zong GJ; Fang CM; Huang Z; Hu XJ; Wu GY; Ma XL (Dove Medical Press, 2023)
Zu-Fei Wu,1,* Wen-Tao Su,2,3,* Shi Chen,4 Bai-Da Xu,2 Gang-Jun Zong,2,3 Cun-Ming Fang,1 Zheng Huang,1 Xue-Jun Hu,1 Gang-Yong Wu,2,3 Xiao-Lin Ma1 1Department of Cardiology, Xuancheng People's Hospital, Xuanchen, Anhui, 242000, People's Republic of China; 2Department of Cardiology, the 904th Hospital of the PLA Joint Logistics Support Force, Wuxi, Jiangsu, 214044, People's Republic of China; 3Department of Cardiology, Wuxi Clinical College of Anhui Medical University, Wuxi, Jiangsu, 214044, People's Republic of China; 4Department of Cardiology, Wuxi No.5 People's Hospital, Wuxi, Jiangsu, 214044, People's Republic of China*These authors contributed equally to this workCorrespondence: Gang-Yong Wu, Department of Cardiology, the 904th Hospital of the PLA Joint Logistics Support Force, Wuxi, Jiangsu, 214044, People's Republic of China, Email wuwangyi520@sina.comObjective: To investigate the correlation between serum parathyroid hormone (PTH) levels and in-hospital major adverse cardiovascular events (MACE) in patients with acute ST-segment elevation myocardial infarction (STEMI) after primary percutaneous coronary intervention (PCI), and establish a risk prediction model based on parameters such as PTH for in-hospital MACE.Methods: This observational retrospective study consecutively enrolled 340 patients who underwent primary PCI for STEMI between January 2016 and December 2020, divided into a MACE group (n=92) and a control group (n=248). The least absolute shrinkage and selection operator (LASSO) and logistic regression analyses were used to determine the risk factors for MACE after primary PCI. The rms package in R-studio statistical software was used to construct a nomogram, to detect the line chart C-index, and to draw a calibration curve. The decision curve analysis (DCA) method was used to evaluate the clinical application value and net benefit.Results: Correlation analysis revealed that PTH level positively correlated with the occurrence of in-hospital MACE. Receiver operating characteristic curve analyses revealed that PTH had a good predictive value for in-hospital MACE. Multivariate logistic regression analysis indicated that Killip class II-IV, and FBG were independently associated with in-hospital MACE after primary PCI. A nomogram model was constructed using the above parameters. The model C-index was 0.894 and the calibration curve indicated that the model was well calibrated. The DCA curve suggested that the nomogram model was better than TIMI score model in terms of net clinical benefit.Conclusion: Serum PTH levels in patients with STEMI are associated with in-hospital MACE after primary PCI, and the nomogram risk prediction model based on PTH demonstrated good predictive ability with obvious clinical practical value.Keywords: parathyroid hormone, acute ST-segment elevation myocardial infarction, percutaneous coronary intervention, nomograms